Environmental sustainability model and biodiversity preservation in Central Rhodopes - Grigorova, Zlatka; Arabsk, Ekaterina (Journal of Economic Development, Environment and People, 2013)
The paper examines the significance, opportunities and ways of biodiversity preservation and sustainable use of natural resources in the central region of the mountain of Rhodopes in Bulgaria. The proposed integrated model of recommendations embraces the following issues: preservation of rare, in danger of extinction and protected plant and animal species and their habitats; implementation of approved environmentally friendly practices in plant growing and animal husbandry; sustainable use of forest, hunting and fishing resources; knowledge, capacity building and motivation in applying measures for sustainable development. In fact that model is composed of many components and considers a number of important aspects. Its application will contribute to the sustainable use of natural resources and preserved biodiversity for future generations.